Kedudukan Hukum Anak Diluar Kawin dalam Mendapatkan suatu Warisan - Billy Verian Salim (Fakultas Hukum Universitas Islam Jember, 2019)
The inheritance law is a rule governing the legal consequences of a person's death against theintangible property: the transfer of wealth from the heir to the heirs. Either in the relationshipof their fellow heirs or between them and the third party. The child is still open to theopportunity to inherit the property of his parents, with the record he has been recognized byhis ayah-ibunya, while the right to justify the mother's possessions by the law is determinedautomatically without the need for a Recognition. Despite being born out of a legitimatemarriage, the acknowledged child of marriage is a hereditary heir.Keywords : law, child out of marriage, inheritance